Enhanced peak growth of global vegetation and its key mechanisms. Issue 12 (December 2018) - Huang, Kun; Xia, Jianyang; Wang, Yingping; Ahlström, Anders; Chen, Jiquan; Cook, Robert; Cui, Erqian; Fang, Yuanyuan; Fisher, Joshua; Huntzinger, Deborah; Li, Zhao; Michalak, Anna; et al.
Abstract The annual peak growth of vegetation is critical in characterizing the capacity of terrestrial ecosystem productivity and shaping the seasonality of atmospheric CO2 concentrations. The recent greening of global lands suggests an increasing trend of terrestrial vegetation growth, but whether or not the peak growth has been globally enhanced still remains unclear. Here, we use two global datasets of gross primary productivity (GPP) and a satellite-derived Normalized Difference Vegetation Index (NDVI) to characterize recent changes in annual peak vegetation growth (that is, GPPmax and NDVImax ). We demonstrate that the peak in the growth of global vegetation has been linearly increasing during the past three decades. About 65% of the NDVImax variation is evenly explained by expanding croplands (21%), rising CO2 (22%) and intensifying nitrogen deposition (22%). The contribution of expanding croplands to the peak growth trend is substantiated by measurements from eddy-flux towers, sun-induced chlorophyll fluorescence and a global database of plant traits, all of which demonstrate that croplands have a higher photosynthetic capacity than other vegetation types. The large contribution of CO2 is also supported by a meta-analysis of 466 manipulative experiments and 15 terrestrial biosphere models. Furthermore, we show that the contribution of GPPmax to the change in annual GPP is less in the tropics than in other regions. These multiple lines of evidence reveal an increasing trend in the peak growth of global vegetation. The findings highlight the important roles of agricultural intensification and atmospheric changes in reshaping the seasonality of global vegetation growth. Combining two global datasets, the authors show that peak vegetation growth has been increasing linearly for the past 30 years, with similar proportions of NDVI variation attributable to expanding croplands, rising CO2 and intensifying nitrogen deposition.